Adjusting ferritin concentrations for inflammation: Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project - Namaste, Sorrel M. L.; Rohner, Fabian; Huang, Jin; Bhushan, Nivedita L.; Flores-Ayala, Rafael; Kupka, Roland; Mei, Zuguo; Rawat, Rahul; Williams, Anne M.; Raiten, Daniel J.; Northrop-Clewes, Christine A.; Suchdev, Parminder S. (Elsevier, 2017)
Background: Total body iron (TBI) that is calculated from ferritin and soluble transferrin receptor (sTfR) allows for the evaluation of the full range of iron status from deficiency to excess. However, both ferritin and sTfR are affected by inflammation and malaria, which may require a statistical adjustment. TBI has been used to assess iron status in the United States, but its use worldwide and in settings with inflammation has been limited.